Cassava, yam, sweet potato and ñampi starch: functional properties and possible applications in the food industry. - Vargas-Aguilar, Pedro (2013)
A technical review was conducted to related physical and chemical properties of flours and starches from cassava, yams, taro and sweet potato. Amyloseamylopectin content, viscosity, nutritional value and fiber, were studied to relate them with starch functional properties. A relationship was obtained between amylose-amylopectin, viscosity and fiber content with the digestibility of those starches and the glycemic index values. The use of fermentation to enhance the nutritional value of these starches is known. Starch fermentation allows the production of gluten-free bread and energy drinks as an option to diversify products. It was also observed the relationship between the starch viscosity and the fat absorption in fried foods.